The Added Value of Bloodpool SPECT/CT in Painful Non-Operated Foot and Ankle Undiagnosed With Standard Three-Phase Bone Scintigraphy - Cuvilliers, Cécile; Palard-Novello, Xavier; Pontoizeau, Clémence; Meneret, Pierre; Devillers, Anne; Le Jeune, Florence; Girard, Antoine (Frontiers in Medicine, 2021)
Purpose: To evaluate the interest of adding a bloodpool SPECT/CT to standard three-phase bone scintigraphy (BS) for etiological diagnosis of subacute and chronic lower extremity pains. Methods: We prospectively included patients addressed for pain of lower extremities lasting for at least 6 weeks, without previous surgery. They underwent a standard three-phase BS including late phase SPECT/CT, modified with an additional bloodpool SPECT/CT acquisition. Two independent physicians interpreted the images provided by both protocols. Diagnostic conclusion, diagnostic confidence and interrater agreements were compared. Results: One hundred and eighteen lower extremities from 113 patients were analyzed (71 men, median age of 53 years). Adding bloodpool SPECT/CT to standard three-phase BS changed diagnostic conclusions in 24.6% (29/118) of lower extremities. The modified protocol revealed at least one diagnostic conclusion explaining the pain in 89% of extremities, rather than 83.1% with the standard protocol (p=0.02). Tendinopathies were diagnosed in 12.7% of lower extremities, rather than 4.2% with standard BS (p=0.002). Adding bloodpool SPECT/CT substantially increased overall confidence of each reader (p<0.001). Inter-reader agreement was not significantly impacted. Conclusion: Adding bloodpool SPECT/CT to standard three-phase BS impacted diagnostic conclusion in a quarter of the patients with painful lower extremities, notably by revealing significantly more tendonitis.